Impact evaluation of approaches to strengthen health facility operation and management committees in Nepal: baseline report - Fehringer, Jassica (USAID ; RIDA International Research Input and Development Action ; Institute for Social & Environmental Research ; Measure Evaluation, 2015)
EXECUTIVE SUMMARY Introduction: This baseline report is a product of a partnership to design, implement, and evaluate a scalable capacity strengthening intervention for Health Facility Operation and Management Committees (HFOMCs) to ensure issues related to gender and social inclusion (GESI) are addressed as part of the delivery of quality government health services in maternal, newborn, and child health (MNCH) as well as family planning (FP) services. The Gender, Policy, and Measurement Program (GPM), implemented by the Health Policy Project (HPP) and MEASURE Evaluation, partnered with Suaahara, a community-focused program dedicated to improving the health of pregnant and lactating women and children less than two years of age. Suaahara and GPM are integrating GESI and community participation components into the existing government of Nepal (GON) guidelines, processes, and training for HFOMCs. The Strengthening HFOMCs through a Community Engagement Approach project (hereafter referred to as strengthening HFOMCs project) includes two capacity strengthening approaches to be evaluated: GESI HFOMC Training and GESI HFOMC Training + Community Engagement. Under GPM, MEASURE Evaluation developed the mixed methods design for the impact evaluation of Strengthening HFOMCs. The aim of the evaluation is to understand the value added from including GESI and community engagement intervention components on household and community level health outcomes, as well as on health care utilization of women and children under two years old in Nepal. Using quantitative baseline and endline data from household, individual, and community surveys, and a variety of qualitative methods, the evaluation will compare the effectiveness of Approach A with the effectiveness of Approach B, which are being implemented in Syangja and Baglung, respectively. A third arm (in Parbat) will serve as the control, in which no intervention activities will be implemented. MEASURE Evaluation led the baseline data collection for the impact evaluation. Local Nepal data collection partners, The Institute for Social and Environmental Research-Nepal (ISER-N) and Research Inputs & Development Internatonal (RIDA), carried out quantitative and qualitative data collection, respectively, from July 2014 to October 2014. This report summarizes key findings from that baseline quantitative and qualitative data. The endline data collection and subsequent analyses, using both baseline and endline data to determine the impact of the intervention approaches, will be carried out in 2016.